KARAKTERISASI GELATIN KULIT IKAN NILA (Oreochromis niloticus) DAN APLIKASINYA DALAM PERMEN JELLY - , EVI SETIYOWATI, Dr. Yudi Pranoto, S.TP, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Tilapia (Oreochromis niloticus) fish skin is a by product of fish processing industry. Tilapia skin used as materials for gelatin because it contains collagen. This study was conducted to determine the characteristics of tilapia fish skin gelatin and the application on jelly candy. In this study, tilapia fish skin gelatin obtained by the extraction process at temperature 80Â°C for 3 hours. Fish skin gelatin was applied to the jelly candy with different concentrations of gelatin addition of 8 , 10 and 12%. Jelly candy of tilapia skin gelatin compared with commercial gelatin jelly candy. The results showed that the yield of tilapia fish skin gelatin is 29,44%. The gel strength of tilapia skin gelatin is 184,61 g Bloom and viscosity is 11,7 cPs with melying point 30,1Â°C. The gel strength and viscosity tilapia fish skin gelatin is higher than commercial gelatin which has the gel strength 183,68 g Bloom and viscosity 10,7 cPs, however the melting point of tilapia skin gelatin is lower than the comercial gelatin. Functional properties of gelatin showed that the higher concentration of gelatin (1, 2 and 3% w/v), then emulsion stability, foam stability and foaming expansion increasing. Physical and chemical characteristics increase with the higher concentration of gelatin is added to the formulation. The results of sensory evaluation in jelly candy gelatin showed the significant difference (P<0,05) on the color, taste and texture of gelatin jelly candy with the various concentration of tilapia skin gelatin which is added. There is no significant difference of the smell of jelly candy gelatin (P>0,05). Overall, the acceptance panelists showed that skin gelatin jelly candy with the addition 8% tilapia skin gelatin is chosen by the panelist.